Between scientific publication and public perception: Some economic remarks on the allocation of time in science - Florian Follert; Chantal Naumann; Lutz Thieme (Europäisches Institut für Sozioökonomie e. V., 2020)
Like every other human being, scientists also have to allocate their scarce resources of time and production according to their personal preferences. Today's scientific system is domina-ted by different (external) incentives that influence a researcher's decisions. With respect to the individual research strategy, there seems to be a conflict between scientific rigor and prac-tical relevance. In addition, only certain scientific results actually find their way into the ge-neral public. We assume therefore that the use of virological and economic expertise are two different forms of reception of science by another social sphere. If our assumption is correct, the question arises as to how such rules of reception are formed and stabilized. This question will be investigated in the present paper. With regard to his or her publication strategy, the scientist therefore has to decide interdependently. Based on the economic approach in general, and Gary S. Becker's theory of time allocation specifically, we develop a simple model to ex-plain scientific decision-making behavior. We derive several implications with regard to a strategy on time allocation in research processes, and thus contribute to a better understanding of scientific decision-making processes. In our paper, we concentrate on the general conditions in (business) economics, but the findings can also be applied to other (human) sciences. In order to be as up-to-date as possible, we take an additional look at the role of science in the current COVID-19 crisis as well.
urn:nbn:de:bsz:291–ds-324116; hdl:20.500.11880/29784
Keywords: 330; economics of science; allocation of time; publication strategy; scientific system; COVID-19; Zeitallokation